404 The importance of FcγRIIA in antibody-mediated neurovascular thrombosis. (14th December 2022) - Laroche, Audrée; Carrier, Micaël; Soulet, Denis; Bazin, Marc; Levesque, Tania; Allaeys, Isabelle; Vallières, Nicolas; Gunzer, Matthias; Flamand, Louis; Lacroix, Steve; Tremblay, Marie-Ève; Fortin, Paul R; et al.
Abstract : Systemic lupus erythematosus (SLE) is an autoimmune disease that damages many organs and tissues. SLE is characterized by the production of autoantibodies and the presence of circulating immune complexes (ICs) in blood. Neuropsychiatric lupus erythematosus (NPSLE) refers to the neurological and psychiatric symptoms directly related to SLE. Alterations in the blood-brain barrier (BBB) and presence of IgG antibodies have been observed in the brain of individuals affected by NPSLE. ICs bind Fcγ receptors (FcγRs), which signaling can play a major role in inflammation and thrombotic events. FcγRIIA receptor is expressed by many immune cells, such as platelets and neutrophils in humans, but it is absent in mice. This explains in part why the interactions of platelets and neutrophils with the brain vasculature endothelium in response to ICs have never been investigated. In this study, we used nanoscale-resolution chip mapping scanning electron microscopy to study the brain vasculature of lupus-prone mice expressing the FcγRIIA transgene (NZB/NZWF1.FcγRIIA TGN ). We found neutrophils (figure 1A), platelets (figure 1 B-C) and immune complexes (figure 1C) adhered to the endothelium of the brain vasculature. To visualize and quantify at the cellular level the events taking place in the brain vasculature in response to systemic administration of surrogate ICs, we generated Ly6gCre +/- ::Rosa26-TdT +/- ::CD41-YFP +/- mice expressing the FcγRIIA transgene and fluorescence in neutrophils (red) and platelets (yellow). Using real-time videomicroscopy to capture high velocity events and an unbiased computer assisted analysis approach, we provide images and quantifications of the cellular responses downstream of FcγRIIA stimulation. We observed platelet aggregation and neutrophil adhesion to blood vessel walls in response to ICs, only in FcγRIIA TGN mice. Moreover, stable and transient interactions between platelets and neutrophils were captured in real time. Taken together, the results highlight the importance of the FcγRIIA receptor in neutrophil adhesion to the BBB in response to ICs and suggest the potential implication of neutrophils and platelets in mediating alterations of the BBB in NPSLE. This study puts forward an imaging and quantifying approach in a quadruple transgenic mouse model that can be utilized for the study of the pathogenic roles of ICs disease.